2011
DOI: 10.1183/09031936.00134410
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension diagnosed by right heart catheterisation in sickle cell disease

Abstract: Recent studies have recognised the importance of pulmonary hypertension (PH) in sickle cell disease (SCD). The aim of this study was to determine the prevalence and prognostic impact of PH and its features in patients with SCD.80 patients with SCD underwent baseline clinical evaluation, laboratory testing, 6-min walk tests (6MWTs) and echocardiography. Patients with a peak tricuspid regurgitant jet velocity (TRV) of o2.5 m?s -1 were further evaluated through right heart catheterisation (RHC) to assure the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
224
2
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(261 citation statements)
references
References 30 publications
18
224
2
10
Order By: Relevance
“…118,127,[129][130][131] Among these complications, PH occurs in 6%-10% of adults with SCD, and the presence of PH is associated with significant increase in the risk of death in these patients. [132][133][134][135] Although the etiology of PH in patients with SCD is multifactorial, including pulmonary arterial hypertension (PAH), pulmonary venous hypertension, and chronic thromboembolic disease, data suggest that mortality in adults with SCD and PH is proportional to the severity of precapillary PH. 136 Transcriptome analysis, PH, and the hypoxic response in SCD Despite SCD's Mendelian inheritance, the clinical course of SCD patients is highly variable.…”
Section: Ph In Scdmentioning
confidence: 99%
“…118,127,[129][130][131] Among these complications, PH occurs in 6%-10% of adults with SCD, and the presence of PH is associated with significant increase in the risk of death in these patients. [132][133][134][135] Although the etiology of PH in patients with SCD is multifactorial, including pulmonary arterial hypertension (PAH), pulmonary venous hypertension, and chronic thromboembolic disease, data suggest that mortality in adults with SCD and PH is proportional to the severity of precapillary PH. 136 Transcriptome analysis, PH, and the hypoxic response in SCD Despite SCD's Mendelian inheritance, the clinical course of SCD patients is highly variable.…”
Section: Ph In Scdmentioning
confidence: 99%
“…5 Pulmonary arterial hypertension (PAH) is a common chronic pulmonary complication of SCD in autopsy studies 6,7 and has a prevalence ranging from 6% to 11% when measured by the gold standard, right heart catheterization. [8][9][10][11] Elevated tricuspid regurgitant jet velocity (TRV), an echocardiographic surrogate of pulmonary artery systolic pressure elevation, is associated with increased mortality in SCD, 12,13 and in a recent series where patients with elevated TRV had confirmatory right heart catheterization, pulmonary hypertension resulted in a 37% 6-year mortality rate. 10 Treatment of SCDassociated PAH is limited, and attempts at expanding accepted PAH treatments to this subset of patients has led to unexpected complications.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of elevated TRV using echocardiography is estimated to be 25-30% among SCA patients and 10-25% in those with genotype SC 6,8,11 . However, studies have reported that only about 6-11% of patients with TRV ≥ 2.5m/s on ECHO have confirmed pulmonary hypertension on right heart catheterization 12,13 . Notwithstanding, elevated TRV ≥ 2.5m/s in sickle cell patients has been significantly associated with decreased exercise tolerance and increased mortality estimated to be about 40% at 40 months of follow-up and is therefore considered an independent risk factor for death among these patients 6,14,15 .…”
Section: Introductionmentioning
confidence: 99%